Probiotics and Bacteriocins Against SARS-CoV-2: Therapeutic Frontiers and Mechanistic Insights - Simeng Sun; Xinyue Guo; Simeng Liu; Shuhong Wu; Lei Ma; Hongru Yang (Probiotics and Antimicrobial Proteins, 2026)

Comparative genomics reveals population structure and ecological adaptation in Lactobacillus helveticus - Haimin Hu; Jiao Wu; Jiaqi Sun; Simeng Wang; Jinhui Liu; Tong Dan (Food Research International, 2026)

Comprehensive single-cell profiling uncovers TsMHC-II expression predicting response to neoadjuvant immunotherapy in gastric cancer - Zhiyuan Xu; Zhichun Tang; Simeng Hu; Litao Yang; Jingli Xu; Pengfei Yu; Yian Du; Yanqiang Zhang; Jiahui Chen; Xiaoxiao Wu; Siwei Pan; ShengJie Zhang; et al. (Science Bulletin, 2026)

Insights into the phosphate stabilization and removal mechanism enabled by phosphogypsum-fly ash ceramsite - Simeng Gan; Zhaorui Li; Yunkang Zhang; Fei Wang; Xiaofeng Huang; Yixing Ma; Quxiu Dai; Ping Ning; Kai Li; Xin Sun (Process Safety and Environmental Protection, 2026)

Long-term scenarios for climate adaptation of cotton crops in China, considering multidimensional biophysical and socio-economic scenario analysis - Simeng Guo; Fengqi Wu; Yuhan Wang; Jian Wang; Zhenggui Zhang; Zhanlei Pan; Chenxi Chong; Pengcheng Li; Weibin Huang; Guilan Sun; Xin Li; Shuchen Wang; et al. (Journal of Cleaner Production, 2026)

Chitin nanocrystal/carboxymethyl cellulose bilayer emulsion with rigid inner layer and flexible outer shell for ultra-stable encapsulation of fish oil - Yufei Sun; Qianxi Deng; Simeng Ji; Yuewen Li; Kao Wu; Ying Kuang; Fatang Jiang; Pengpeng Deng (Carbohydrate Polymers, 2025)

A Novel COLREGs-Based Automatic Berthing Scheme for Autonomous Surface Vessels - Shouzheng Yuan; Gongwu Sun; Yunqian He; Yuxin Sun; Simeng Song; Wanyuan Zhang; Huifeng Jiao (Journal of Marine Science and Engineering, 2025)
This paper tackles the highly challenging problem of automatic berthing for autonomous surface vessels (ASVs), encompassing trajectory planning, trajectory tracking, and collision avoidance. Firstly, a novel A* algorithm integrated with a quasi-uniform B-spline and quadratic interpolation method (A*QB) is proposed for generating a smooth trajectory from the initial position to the berth, utilizing an offline-generated scaled map. Secondly, the optimal nonlinear model predictive control (NMPC)-based trajectory-tracking framework is established, incorporating the model’s uncertainty, the input saturation, and environmental disturbances, based on a 3-DOF model of a ship. Finally, considering the collision risks during port berthing, a COLREGs-based collision avoidance method is investigated. Consequently, a novel trajectory-tracking and COLREGs-based collision avoidance (TTCCA) scheme is proposed, ensuring that the ASV navigates along the desired trajectory, safely avoids both static and dynamic obstacles, and successfully reaches the berth. To validate the TTCCA approach, numerical simulations are conducted across four scenarios with comparisons to existing methods. The experimental results demonstrate the effectiveness and superiority of the proposed scheme.

High strength, gas barrier and hydrophobic konjac glucomannan/glutenin films with semi-interpenetrating network for cherry tomato preservation - Pengpeng Deng; Zihao Wang; Yuewen Li; Simeng Ji; Yufei Sun; Qianxi Deng; Juanjuan Chen; Fatang Jiang (Food Hydrocolloids, 2025)

Necroptosis in obesity: a complex cell death event - Zunhai Liu; Simeng Wang; Wentao Wang; Rui Lv; Chao Sun (Apoptosis, 2025)

Recent advances on transport and transformation mechanism of nanoplastics in lung cells - Simeng Zhang; Hangxi Zhang; Yichen Li; Zhiwei Sun; Yueyue Chen (Science of The Total Environment, 2024)

Exposure to volatile organic compounds and growth indicators in adolescents: Unveiling the association and potential intervention strategies - Jingyi Ren; Xiaoya Sun; Zhenao Zhang; Huanting Pei; Yadong Zhang; Rui Wen; Simeng Qiao; Zidan Wang; Weican Zhang; Jinshi Zuo; Yuxia Ma (Journal of Hazardous Materials, 2024)

Adsorption Properties of UiO-66/Wood Hybrid Adsorbent for Organic Dye Removal - Sun Chang; Yao Simeng; Qin Chengrong; Long Zhu (Water, Air, & Soil Pollution, 2023)

EMPMR berthing scheme: A novel event-triggered motion planning and motion replanning scheme for unmanned surface vessels - Shouzheng Yuan; Zhilin Liu; Yuxin Sun; Simeng Song; Zhongxin Wang; Linhe Zheng (Ocean Engineering, 2023)

Autophagy May Be Involved in Fluoride-Induced Learning Impairment in Rats - Chengzhi Zhang; Simeng Huo; Yumei Fan; Yanhui Gao; Yanmei Yang; Dianjun Sun (Biological Trace Element Research, 2020)

FRZB1 rs2242070 polymorphisms is associated with brick tea type skeletal fluorosis in Kazakhs, but not in Tibetans, China - Yanmei Yang; Qiaoshi Zhao; Yang Liu; Xiaona Liu; Yanru Chu; Huazhu Yan; Yumei Fan; Simeng Huo; Limei Wang; Qun Lou; Ning Guo; Dianjun Sun; et al. (Archives of Toxicology, 2018)

Erratum to: The role of particle size of glyburide crystals in improving its oral absorption - Wenqian Yang; Yongjun Wang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

The role of particle size of glyburide crystals in improving its oral absorption - Yongjun Wang; Wenqian Yang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)